Identifikasi dan Potensi Tumbuhan Obat di Kawasan Ekowisata Gunung Api Purba Nglanggeran, Kabupaten Gunung Kidul, Provinsi Daerah Istimewa Yogyakarta - Robertus Anugerah Gemilang; Karti Rahayu Kusumaningsih (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2025)
Medicinal plants have long been utilized by the community, especially those living around forest. The Nglanggeran Ancient Volcano Ecotourism Area, Gunung Kidul Regency, Yogyakarta is an ecotourism with ​​48 Hectares area that is covered with various types of medicinal plants whose potential is unknown. This study aims to identify the types and determine the potential of medicinal plants in the Nglanggeran Ancient Volcano Ecotourism Area, Gunung Kidul Regency, Yogyakarta. Sampling was carried out by creating a 20 x 20 meter plot using the Purposive Random Sampling method. Quantitative analysis was used to calculate the density, frequency, dominance, Importance Value Index (INP), and Species Diversity Index (H’) of medicinal plants at various life stages. Result of the research showed that there were 28 types of medicinal plants originating from 22 families. The most commonly found medicinal plant species among trees was mahogany (Swietenia macrophylla - Meliaceae family) with 34 individuals, and among herbs was Elephantopus scaber - Asteraceae family with 39 individuals. The highest Important Value Index at the tree level was S. macrophylla at 253.61, pole level was Annona muricata at 140.83%, sapling level was S. macrophylla at 41.35%, and seedling level was Elephantopus scaber at 41.79%. The Species Diversity Index (H') at the seedling level was 2.552, saplings at 2.021, and poles at 1.429, which is considered moderate, while at the tree level it was 0.509, which is considered low.